Change To A State Islamic University In Indonesia And The Quality Of Education Services - Ahmad Qurtubi (Indikator Pendidikan Indonesia, 2018)
Modernization Islamic Higher can make these adjustments, it will create a new college paradigm. UIN from IAIN and IAIN from STAIN are useless unless changed. True UIN development philosophy is not simply to build an independent worker, but also to develop scientific identity. UIN's science and technology don't castrate Islamic studies programs or its identity. UIN, as a college-based Islamic science, must establish a strong science. Integrate S1, S2, and S3 into majors and courses. Globalization of education policy execution should modify UIN's academic climate to establish Islam's science. Pride in the college motto UIN as a pioneer and excel in the field of Islamic is more than